One dimensional analysis of thermoelement exposed to lateral heat transfer as a wall in MEMS-Based thermoelectrically controlled micronozzle - Mohammed Idres, Moumen; Hasan, Amar; Kafafy, Raed (2011)
A new technology for micropropulsion which uses thermoelectric elements to control the wall temperature of microthrusters is under development at the International Islamic University Malaysia. In this new technology,solid state walls act as either flow heater or cooler based on the local flow Mach number to achieve maximum acceleration of the flow throughout the micronozzle. This technique is believed to improve the performance of low-Reynolds-number microthrusters which typically suffer from high viscous losses and low thrust efficiency. Extensive analytical and experimental investigation is still required to assess the potential of the new technology. In the current work, we focus on effect of gas flowing on lateral side of thermoelement formed as walls of the micronozzle and the thermoelectric Peltier effect is induced in the solid-state walls. The model of heat transfer by conduction opposites to Peltier effect and heat dissipation to a flowing gas at the lateral of TE is built, other energy sources like Joule heating and Seebeck effect are also included. A general energy equation of one dimensional heat flow in a TE subjected to electrical field and heat convection at the lateral side is written, then it is solved for temperature distribution in many cases; effect of convection heat transfer coefficient, Joule heating, and choosing boundary conditions are tested analytically for constant material electrical and thermal properties. Numerical solution is established for the energy equation of non uniform shape of TE governing temperature distribution Two parameters which play important role in the thermal performance of TE are identified. These are the Heat Resistance Ratio; ratio of longitudinal conduction resistance to lateral convection resistance, and Energy Growing Ratio; ratio of Joule heating to Fourier conducted heat. The effects of varying these two parameters as well as TE geometry have been investigated thoroughly and the results are presented in the form of charts to assist the design and material selection of the TE. TE can supply heat exchange then reverse heat exchange direction to a fluid passing on its surface in any application rather than micronozzle along flow stream consequently.